HMENA isoforms impact NSCLC patient outcome through fibronectin/β1 integrin axis. Issue 42 (18th October 2018) - Di Modugno, Francesca; Spada, Sheila; Palermo, Belinda; Visca, Paolo; Iapicca, Pierluigi; Di Carlo, Anna; Antoniani, Barbara; Sperduti, Isabella; Di Benedetto, Anna; Terrenato, Irene; Mottolese, Marcella; Gandolfi, Francesco; et al.
Abstract We demonstrated previously that the splicing of the actin regulator, hMENA, generates two alternatively expressed isoforms, hMENA11a and hMENAΔv6, which have opposite functions in cell invasiveness. Their mechanisms of action have remained unclear. Here we report two major findings: (i) hMENA regulates β1 integrin expression. This was shown by depleting total hMENA, which led to loss of nuclear expression of serum response factor (SRF)-coactivator myocardin-related transcription factor 1 (MRTF-A), leading to an increase in the G-actin/F-actin ratio crucial for MRTF-A localization. This in turn inhibited SRF activity and the expression of its target gene β1 integrin. (ii) hMENA11a reduces and hMENAΔv6 increases β1 integrin activation and signaling. Moreover, exogenous expression of hMENA11a in hMENAΔv6-positive cancer cells dramatically reduces secretion of extracellular matrix (ECM) components, including β1 integrin ligands and metalloproteinases. On the other hand, overexpression of the pro-invasive hMENAΔv6 increases fibronectin production. In primary tumors high hMENA11a correlates with low stromal fibronectin and a favorable clinical outcome of early node-negative non-small-cell lung cancer patients. These data provide new insights into the roles of hMENA11a and hMENAΔv6 in the druggable β1 integrin-ECM signaling axis and allow stratification of patient risk, guiding their clinical management.